(untitled) (Biomedical Research and Therapy, 2017)
The hearing is an important sensation of all living organism to maintain his or her life mainly in human. Any distortion to it leads to hearing impairment. Hearing loss (HL) can be congenital or acquired. It can be syndromic; HL associated with other abnormalities or non-syndromic, HL is not associated with any other anomalies. Hearing impairment have mostly autosomal recessive loci, but can be autosomal dominant, X-linked, and mitochondrial. Acquired HL can be genetic or environmental factors based. Age-related HL is acquired hearing loss occur in aged population. Its prevalence rate increases with age. Genetic of presbycusis is not well-known, but NAT2*6A polymorphism, SNPs in KCNQ4, grainy head-like 2 gene, Glutamate receptor-7 gene, 4977-bp mt-DNA deletion in human and 4834-bp mtDNA deletion in rodents were identified. Different strains of mice are developed like C57BL/6J, CBA/CaJ, DBA/2J, BALB/cJ and Fisher 344 albino rats mainly used as models to study HL and presbycusis. Like other disorders have complete treatment, but HL cannot be completely treated. However some attempts can be made for its betterment by using hearing aid devices, surgical and pharmaceutical treatments. In future stem cells and gene therapy will be the affective methods to treat congenital hearing impairment and presbycusis.